Pemanfaatan Sampah Bahan Habis Pakai Non-Medis Laboratorium Ketrampilan Klinik (SKILLS LAB) Sebagai Modifikasi Alat Peraga Sederhana Skill Mandiri - P Patmawati; Fadilah Hidayati (Jurnal Pengelolaan Laboratorium Pendidikan, 2020)
The Skills Lab is a facility where students can practice the skills they need, which is not a real context between doctor and patient. Practicum in the Clinical Skills Laboratory and OSCE uses non-infectious non-medical consumables. The stages of making modification props are carried out in several stages including: collecting and sorting non-infectious non-medical consumables. Disinfection of non-medical consumables that are non-infectious with antiseptics. The produced props include gloves used as prepuce in circumcision beads. Modified infusion plastic bottles resemble human nails we use for nail extraction skills. The IV line can be modified as a vein in the bead, this is used for the sexy vein skill in the beaded IV. Abocart needle (neddle) is used for NGT or usually called sonde for experimental animals. Rubber infusion hose is used as an LED tube rubber ball in Clinical Pathology practicum.